Store format influence on customer perception of the store environment - Marques, S.; Santos, M-C. (International Journal of Applied Behavioral Economics (IJABE), 2012)
This study compares client perceptions of the global in-store environment applied to different retail store formats. Literature has shown that certain store attributes are important strategic differentiation tools for grocery retailers. A retail atmosphere can lead to success or failure of a business. Previous studies have neglected the current trend to the coexistence of different retail formats, under different brands but within the same organization. In these cases, a multi-banner company needs to customize the atmosphere to its customers in order to gain attention. This research is about the influence of the store format on the servicescape of the grocery retail stores. A survey was conducted of 302 hyper and supermarket customers. A range of atmospherics variables were considered, including some less studied, such as temperature and cleanliness. The results show that all the dependent variables are sensitive to store format, except cleanliness.